Organic acids bioproduction from corn fiber using Actinobacillus succinogenes - Mugisha, Christian (Kansas State University, 2024)
Succinic acid (SA) and lactic acid (LA) are organic acids which are used to synthesize high value industry chemicals, which have applications in the food, agricultural, chemical, and pharmaceutical industries. Currently, these acids are produced primarily from fossil-fuel feedstocks, which are nonrenewable. This chemical process is expensive and ecologically questionable as it increases carbon footprints. Since SA and LA are intermediates in many living organisms, they can be produced biologically using a variety of microorganisms. One of the most promising microorganisms for SA and LA production is Actinobacillus succinogenes due to its resistance to these acids and other inhibitors, and its ability to utilize a variety of sugars. The aims of this study included SA bioproduction, investigation of the effect of N₂ and CO₂ bubbling on LA production, and LA bioproduction from corn fiber (CF) hydrolysates using A. succinogenes. CF is a byproduct of the dry grind corn ethanol process and has minimal lignin and high polysaccharide content. To produce SA and LA, CF was pretreated and hydrolyzed using enzyme. The hydrolysates were later fermented using A. succinogenes. When a control mimicking the sugars in hydrolysates was fermented, a maximum SA concentration of 25.3 g/L with a yield of 0.44 g/g sugars was obtained. After 3 months of A. succinogenes storage in 5% DMSO, the cells lost their ability to make SA and started making more LA. Cells in CO₂ bubbled media produced the highest LA concentration of 36.1 g/L LA with a 0.72 g/g glucose. Cells in CO₂ bubbled detoxified hydrolysate produced the highest LA concentration of all hydrolysates (22.5 g/L LA with a 0.57 g/g glucose yield) while cells in CO₂ bubbled control media mimicking the sugars in detoxified hydrolysate produced 28.5 g/L LA with a 0.73 g/g glucose yield. For future studies, better cryopreservation techniques of A. succinogenes will sustain the cells fermentation ability over time.
Keywords: Corn fiber hydrolysate; Actinobacillus succinogenes; Fermentation; Pretreatment; Succinic acid; Lactic acid